Dissolution dynamics of NaCl at the atomic scale. (June 2022) - Guo, Cong; Fu, Mingming; Gong, Caimei; Wu, Sanqin; Zhang, Yuyang; Wang, Zhongping; Wei, Sheng; Liu, Xiaoqing; Wang, Li
Abstract: Insulating films such as sodium chloride (NaCl) are ideal platforms for studying single atoms and single molecules as decoupling layers. The NaCl dissolution process has been extensively studied, and has become an increasingly important scientific problem. However, the understanding of defect dynamics in the NaCl dissolution process at the atomic scale is still in the exploratory stage. Here we imaged the dissociation process of bilayer NaCl islands on an Au (111) surface at the atomic scale using a low-temperature scanning tunneling microscope. We found that water molecules preferentially combined with Na +, and formed Na + hydrates accompanied by Na + vacancy defects. First-principles calculations revealed a small diffusion barrier of Na + hydrates, which contributed to the migration of Na + vacancy defects. The defect density of Na + vacancies increased with extension of the water exposure time, which resulted in a reduction of binding energy of the NaCl system. Calculations revealed that when the number of Na + vacancy defects in a local area reached 35, the binding energy of the NaCl system dropped to zero. Then the NaCl in this area would completely dissociate. This work aids understanding of the NaCl dissolution process at the atomic level, and offers some references for the application and design of insulating films. Graphical abstract: Image 1 Highlights: Defect dynamics in the NaCl dissolution process are observed at the atomic scale. Na  +  vacancy defects migrate randomly due to small diffusion barriers of Na  +  hydrates. Defect density of Na  +  vacancies increases with extension of water exposure time. Extension of water exposure time reduces binding energy of the NaCl system.